Charmonium in nuclear matter and nuclei - Cobos Martinez, J. J.; Tsushima, K.; Krein, G. [UNESP]; Thomas, A. W.; Hernandez, A. S. (Sissa Medialab, 2021)
We present results for the eta(c)-nucleus bound state energies for various nuclei using an effective Lagrangians approach. The attractive potentials for the eta(c) in the nuclear medium originate from the medium-modified intermediate DD* state in the eta(c) self energy, using the local density approximation. Our results suggest that the eta(c) should form bound states with all the nuclei considered.